A certeza da objetividade cobrindo a incerteza da subjetividade: um estudo de caso - a ADIn 3.510/DF e a presença de elementos jurídicos e extrajurídicos na argumentação constitucional - Reis, Silas Mendes dos (2010)
By establishing a foundation for final decisions of merit, judicial authority uses several elements, such as language, interpretation and discourse, which will comprise the content of the sentence or judgment, culminating in the grounds or lack of grounds for the request. However, in collegiate judgments, even if the conclusion of decisions pronounced by judges is the same, the votes rendered take different paths, characterized by the oneness of foundations chosen, even in cases of decisions rendered unanimously. Although there is no uniformity of understanding, the conclusions presented are considered acceptable, with the interpretation made by winning votes prevailing. This dissertation intends to demonstrate the presence of extrajudicial elements in the formation of the judge's conviction, characterized and raised by subjectivity. The certainty of objectivity functions as a cloak spread over subjectivity. The demonstrative method and study of arguments will be used according to the structure elaborated by Chaïm Perelman and also from the perspective of legal and non-legal argumentation found in the judgment of ADIn 3510/DF on the use of embryonic stem cells obtained from human embryos produced by in vitro fertilization and not used in the respective procedure. The study will consist of showing there is a merger of objective and subjective elements in the foundation related to the belief of the legal exegete. It shall be concluded that subjectivity is tied to experience and culture found in the foundation for the votes, encompassing valued judgments and their arbitrary (discretionary) application, implicitly containing intuition. The scope of the dissertation will be a case study (ADIn 3.510/DF) and the validity of the procedure, starting with the choice of a sample of the vote population emanating from the Ministers of the Federal Supreme Court, and checking whether it constitutes an outline of the population of decisions handed down by jurisdictional entities